Plant Defense Responses to Biotic Stress and Its Interplay With Fluctuating Dark/Light Conditions - Iqbal, Zahra; Iqbal, Mohammed Shariq; Hashem, Abeer; Abd_Allah, Elsayed Fathi; Ansari, Mohammad Israil (Frontiers in Plant Science, 2021)
Plants are subjected to a plethora of environmental cues that cause extreme losses to crop productivity. Due to fluctuating environmental conditions, plants encounter difficulties in attaining full genetic potential for growth and reproduction. One such environmental condition is the recurrent attack on plants by herbivores and microbial pathogens. To surmount such attacks, plants have developed a complex array of defense mechanisms. The defense mechanism can be either preformed, where toxic secondary metabolites are stored; or can be inducible, where defense is activated upon detection of an attack. Plants sense biotic stress conditions, activate the regulatory or transcriptional machinery, and eventually generate an appropriate response. Plant defense against pathogen attack is well understood, but the interplay and impact of different signals to generate defense responses against biotic stress still remain elusive. The impact of light and dark signals on biotic stress response is one such area to comprehend. Light and dark alterations not only regulate defense mechanisms impacting plant development and biochemistry but also bestow resistance against invading pathogens. The interaction between plant defense and dark/light environment activates a signaling cascade. This signaling cascade acts as a connecting link between perception of biotic stress, dark/light environment, and generation of an appropriate physiological or biochemical response. The present review highlights molecular responses arising from dark/light fluctuations vis-à-vis elicitation of defense mechanisms in plants.